Pengaruh Kompensasi dan Peran Kepemimpinan terhadap Kinerja Pegawai Dinas PUPR Kab. Karawang - Khairiyah, Sarah; Fadili, Dadan Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine and analyze The Effect of Compensation and The Role of Leadership on The Employee Performace at Dinas PUPR Kab. Karawang. This research used primary data obtained from distributing questionnaires and secondary data obtained adjusted to the literature related to this research. The sample used in this study amounted to 115 people using a non-probability sampling technique with a saturated sampling method. The data analysis technique used are the likert scale analysis and path analysis. Based on the analysis that has been carried out, the correlation coefficient between the compensation variable and the leadership role is 0,645 which means it has a strong, positive, and significant correlation level. The partial effect of compensation variable on employee performance variable at Dinas PUPR Kab. Karawang is 18,9% and the partial effect of the role of leadership variable on employee performance variable is 39,9% which means the role of leadership has bigger effect on employee performance variable than the compensation variable. The simultaneous effect of compensation variable and leadership role variable on employee performance variable is 58,9% while the remaining 41,1% is the contribution of other variables not examined. Keywords : compensation; leadership role; the role of leadership; employee performance